PHYSICAL, CHEMICAL AND SENSORY PROPERTIES OF KENARI (Canariun indicum L.) SHELL LIQUID SMOKE-IMMERSED-BEEF ON DIFFERENT LEVEL OF DILUTION - Yusnaini, Y.; Soeparno, S.; Suryanto, E.; Armunanto, R. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
This research was aimed to study the effect of the dilution level of kenari shell liquid smoke to thephysical, chemical and sensory properties of beef. Longissimus dorsi of beef immersed on Kenari shellliquid smoke on the level of dilution 1x, 2x, 3x, 4x, and 5x during 15 minutes with five replicatesfollowing Randomized Complete Design. The results showed that the higher level of dilution of liquidsmoke kenari shell caused the physical, chemical and sensory properties which get closer to the qualityof the control samples. The level of dilution affected almost all the properties, except the water andprotein content. It was concluded that the lower levels of dilution caused the more affected into thephysical, chemical and sensory properties of beef, except the water and protein content.